Primary ameloblastic carcinoma: literature review with case series - Mahmoud, Sarah Ahmed Mohamed; Amer, Hatem Wael; Mohamed, Sally Ibrahim (Polish Journal of Pathology, 2018)
Ameloblastic carcinoma (AC) is an extremely rare malignant odontogenic tumour arising from odontogenic epithelium. It was classified into primary type and secondary type. A previous study revealed that primary ameloblastic carcinoma cases were associated with more favourable prognosis than secondary cases. The aim of the present work was: to report the clinical, histopathological, immunohistochemical, and ploidy status, and therapeutic details of four cases of primary AC, and to review the literature with regard to clinical, follow-up, prognosis, histopathological, and immunohistochemical information of primary AC. The Medline database was searched using the term ameloblastic carcinoma and primary type. The review of English literature revealed that primary ameloblastic carcinoma favours the posterior mandible with profound male predilection and appears as an ill-defined radiolucency. Metastasis and invasion are more likely to occur in maxillary cases. The treatment of choice is wide surgical resection with or without cervical lymph node dissection. Adjuvant postoperative radiotherapy is beneficial in incomplete resection cases and advanced soft tissue invasion. The most specific diagnostic methods of AC, as concluded from review, are α-SMA in epithelial cells in conjunction with Ki-67 index value and SPF more than 11.5%.